Art experiments as stimulus for cultural creative processes: at the intersection of "positive" and "negative" psychology - Onishchenko, Olena (Ukrainian Cultural Studies, 2024)
Background. The problem of the article is related to the beginning of the 20th century, when the concept of "artistic experiment" became a part of theoretical discourse. It was stimulated by a change of the art paradigm, caused by avant-garde. Such a transformation was based on the exhaustion of romanticism and naturalism and the powerful entry of the aesthetic and artistic principles of symbolism into the European cultural space. The gradual detachment of a part of artists from romanticism and naturalism led to the start of fundamentally new trends that formed the avant-garde movement. The article aims to apply a comparative analysis of "positive" and "negative" types of psychology to reveal the specifics of artistic experiments in the formation and development of the avant-garde movement. Methods. the article uses the potential of such methods as chronological (historicism), analytical (outlining of the components of the research process), historical retrospection (capability to operate with the concept of "negative" psychology), comparative (comparison of "positive – negative psychology"), typological (definition of psychological /mental state of the artist). Results. it is argued that the Franco-Italian-German artists who formed the core of avant-garde did not share the principles of classical arts, absolutizing both the freedom of creativity and its permissiveness. The article emphasizes that representatives of specific aesthetic and artistic trends of avant-garde – cubists, futurists, abstractionists, dadaists, surrealists – supported the spontaneity of the creative process. It was indicated that from the second half of the 19th century, the process of radical transformations can be traced both in the space of European humanities and in the literary and artistic fields. First, a kind of reorientation of the humanities takes place, it activates the interdisciplinary links and the situation of theoretical and practical parity. Second, cinematography emerges as a new kind of art that, relying on scientific and technical progress achievements, confidently "fits" into the cultural context. Third, at the turn of the 19th and 20th centuries, such new professions as film director, film producer, screenwriter, cameraman, sound engineer, etc. emerged and vastly affected a person's worldview by their work. Conclusions. In outlined conditions the role of psychology and psycho-physiology became significantly strengthened. It began to "cooperate" actively with other domains of humanities, in particular, aesthetics and art history.
Keywords: artistic experiment; "positive" and "negative" psychology; cultural studies context